The value of 18F-AlF-NOTATATE PET/CT in restaging high-risk neuroblastoma after chemotherapy - Wang, Han; Zuo, Di; Zheng, Fei; Sun, Yingying; Liu, Yuxuan; Yang, Hao; Wang, Jingfu; Sun, Xiaorong (Frontiers in Medicine, 2025)
PurposeTo evaluate the value of 18F-AlF-NOTATATE PET/CT in restaging high-risk neuroblastoma (NB) after chemotherapy and its advantages over anatomical imaging.Materials and methodsWe retrospectively collected data from high-risk patients with NB who were restaged after chemotherapy using 18F-AlF-NOTATATE PET/CT between June 2021 and June 2022. The histopathological, clinical, and radiographic follow-up results were used as reference standards for the final diagnosis. Patient- and lesion-based analyses were performed. The chi-square test was used to compare the efficacy between 18F-AlF-NOTATATE PET/CT and anatomical imaging for the detection of residual lesions. One-way ANOVA was used to compare the difference between the maximum standard uptake (SUVmax) values of false-positive and true-positive residual lesions in the surgical subgroups.ResultsExactly 159 high-risk patients with NB underwent 18F-AlF-NOTATATE PET/CT restaging. Exactly 134 patients had 634 residual lesions, and the true-positive rate was 88.5%. Among the residual NB lesions, distant and regional lymph node metastases accounted for 86 and 16%, respectively. In the lesion-based analysis, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of 18F-AlF-NOTATATE PET/CT were significantly higher than those of anatomical imaging. In the patient-based analysis, the specificity, PPV, and accuracy of 18F-AlF-NOTATATE PET/CT were also significantly higher. In the surgical subgroup, the SUVmax of false-positive lesions was significantly lower than that of NB.ConclusionThe efficacy of 18F-AlF-NOTATATE PET/CT in restaging high-risk NB after chemotherapy is significantly superior to anatomical imaging. Although, the SUVmax may help identify false-positive lesions, it cannot distinguish benign transformation after NB treatment.